2016
DOI: 10.1080/1478422x.2016.1185568
|View full text |Cite
|
Sign up to set email alerts
|

Impact specimen geometry on T23 and TP347HFG steels behaviour during steam oxidation at harsh conditions

Abstract: Ferritic T23 steel and austenitic TP347HFG steel have been studied with an emphasis on understanding the impact of specimen geometry on their steam oxidation behaviour. The selected materials were tested over a wide range of temperatures from 600 to 750°C. The tests were carried out in 100% steam conditions for 1000 hours. The tests indicated that the 'curvedshaped' specimens show slower mass gain, scale ticking and void nucleation rates than 'bridge-shaped' specimens (with flat and convex surfaces combined). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is well known that high-temperature oxidation in 100% steam is characterized by faster oxidation rates than in dry or humid environments [4]; in addition, the scale formed exhibits different adherence and porosity [5,6] leading to a loss of the protective properties of chromia scale [7]. Under cyclic conditions, the oxidation resistance of ferritic-martensitic steels depends primarily on their chromium content and the rapid formation of a dense protective Cr-rich oxide scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that high-temperature oxidation in 100% steam is characterized by faster oxidation rates than in dry or humid environments [4]; in addition, the scale formed exhibits different adherence and porosity [5,6] leading to a loss of the protective properties of chromia scale [7]. Under cyclic conditions, the oxidation resistance of ferritic-martensitic steels depends primarily on their chromium content and the rapid formation of a dense protective Cr-rich oxide scale.…”
Section: Introductionmentioning
confidence: 99%
“…There are many papers describing the steam oxidation of heat-resistant steel used in USC power plants [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. It is well known that Cr is the indispensable element in heat-resistant steel, with excellent strength and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Viswanathan et al [ 1 ] concluded that steam oxidation of heat-resistant steel was influenced by the heat flux, environment, steam parameter, and alloy compositions. Surface pretreatments and sample geometry also affected the oxidation resistance of steels, such as sandblasting and pre-oxidation treatment [ 1 , 16 , 21 ]. Fry and Piedra [ 22 ] discussed the effect of specimen geometry, steam pressure, and dissolved oxygen of water on the oxidation behavior of heat-resistant steel.…”
Section: Introductionmentioning
confidence: 99%
“…Lukaszewicz conducted a series of studies on the steam oxidation behavior of various materials in the laboratory, in additional, he reported some results from an investigation into the impact of steam flow rates and sample orientation on the steam oxidation of surface ground superheater tube materials. [20][21][22]. However, there are few studies on the comparison of steam oxidation behavior of various austenitic steels in long-term service environment (over 15,000 h).…”
Section: Introductionmentioning
confidence: 99%